Psychometric Properties and Factor Structure of the German Version of the Clinician-Administered PTSD Scale for DSM-5. (September 2020) - Müller-Engelmann, Meike; Schnyder, Ulrich; Dittmann, Clara; Priebe, Kathlen; Bohus, Martin; Thome, Janine; Fydrich, Thomas; Pfaltz, Monique C.; Steil, Regina
The Clinician-Administered PTSD Scale (CAPS) is a widely used diagnostic interview for posttraumatic stress disorder (PTSD). Following fundamental modifications in the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition ( DSM-5 ), the CAPS had to be revised. This study examined the psychometric properties (internal consistency, interrater reliability, convergent and discriminant validity, and structural validity) of the German version of the CAPS-5 in a trauma-exposed sample ( n = 223 with PTSD; n =51 without PTSD). The results demonstrated high internal consistency (αs = .65-.93) and high interrater reliability (ICCs = .81-.89). With regard to convergent and discriminant validity, we found high correlations between the CAPS severity score and both the Posttraumatic Diagnostic Scale sum score ( r = .87) and the Beck Depression Inventory total score ( r = .72). Regarding the underlying factor structure, the hybrid model demonstrated the best fit, followed by the anhedonia model. However, we encountered some nonpositive estimates for the correlations of the latent variables (factors) for both models. The model with the best fit without methodological problems was the externalizing behaviors model, but the results also supported the DSM-5 model. Overall, the results demonstrate that the German version of the CAPS-5 is a psychometrically sound measure.